Influence of Skills and Non-Physical Work Environment on Employee Performance - Rismaya Sulistyowati; Zakky Fahma Auliya (Profesional Muda Cendekia Publishing, 2022)
This research aims to determine the effect of skills and non-physical work environments on the employee performance of UD. Surya Abadi Furniture. This type of research is quantitative research. The data collection method used is to disseminate questionnaires and interviews analyzed with IBM SPSS Software version 25.0. The population used in this study were employees working at UD. Surya Abadi Furnitue with a total of 80. The sample in this study amounted to 73 respondents. The sampling technique used is probability sampling, with a simple random sampling method.The results showed that skills have a significant effect on employee performance, non-physical work environments have a significant effect on employee performance, and non-physical work skills and environments simultaneously effect employee performance